The New Basel Capital Framework and its implementation in the European Union - Frank Dierick; Fatima Pires; Martin Scheicher; Kai Gereon Spitzer (European Central Bank (ECB), 2005)
Following the adoption by the Basel Committee of new capital rules for banks, a process is now taking place in the EU to transpose the rules into Community law and, ultimately, into national legislation. This paper gives an overview of the main issues that relate to the EU implementation, mainly from the perspectives of financial stability and financial integration. Although the EU rules are to a large extent based on the texts of the Basel Committee, modifications have been introduced to account for the specific legal and institutional setting, as well as for some features of the European financial system. The paper gives an overview of these modifications and deals in greater detail with a number of selected topics: the monitoring of procyclicality, the role of the consolidating supervisor and the treatment of real estate lending and covered bonds. The paper concludes with an outlook for the future.
Keywords: G21; G28; 330; Banks; Basel II; capital requirements; financial regulation; financial stability; financial supervision; risk management.; Basler Akkord; Bankrecht; EU-Recht; Bankenaufsicht; EU-Staaten; Basler Akkord